Innovation in Making Buffalo (Bubalus bubalis) Milk Probiotic: Dadih - Ginting, Nurzainah; Mirwandhono, Raden Edhy; Wirawan Siregar, Galih Ari; Sutanto, Wahyudi Himawan; Lin, Yuan Yu (Journal of Buffalo Science, 2026)
Dadih is a traditional, sustainable food made from fermented buffalo milk, passed down from generation to generation on the island of Sumatera for thousands of years. The COVID-19 outbreak has significantly increased demand for buffalo milk, including fermented buffalo milk/dadih in Sumatera due to its nutritional content. Until now, milk fermentation has been carried out using Bambusa verticillata bamboo tube containers. This fermentation process has varied consequences depending on the conditions of each bamboo. Furthermore, bamboo cannot be reused in making dadih, so efforts are underway to find alternative containers for producing dadih, including plastic containers with the addition of a starter culture. This study aimed to identify the optimal conditions for manufacturing dadih in plastic containers using bamboo dadih as the initial culture. The study utilised a factorial completely randomized design comprising two factors. The first factor was the fermentation period, which was 24 to 48 hours. The second factor comprised initial concentrations of 1.5%, 3%, 4.5%, and 6%. At the beginning of the study, dadih was isolated to obtain a dominant culture, which was then purified and identified using the PCR 16S rRNA method-the study analysed chemical quality parameters, including pH, protein content, and total acid. In addition, it evaluated the biological condition by quantifying the overall number of bacterial colonies. The organoleptic characteristics were assessed based on aroma, color, texture, and taste. The PCR results showed that the dominant bacteria were Weissella cibaria. The pH levels across all treatments ranged from 4.53 to 4.62. Furthermore, the protein level decreased as the proportion of starter and the length of fermentation increased. In contrast, the overall acidity level rose as the proportion of starter and duration of fermentation increased. There was an interaction between the fermentation period and dadih concentration. The organoleptic test showed significant differences in texture and taste due to the treatment using a 3% starter and a fermentation time of 24 hours. The study results suggest that fermenting dadih in plastic containers with a 3% starter for 24 hours produces the most desirable organoleptic effects. The colony count of 2.4x108, which is dominantly by Weissela cibaria, indicates that the drink is classified as probiotic.